In vitro Propagation and Callus Formation of Bacopa monnieri (L.) Penn. (Plant Tissue Culture and Biotechnology, 2011)
An important medicinal herb, namely Bacopa monnieri (L.) Penn. showed best results on MS with 1 mg/l IAA and 1 mg/l IBA for culture initiation, multiple shoot proliferation, bud breakage, shoot length, shoot numbers and cluster formation. For rooting the best result was obtained on MS solidified with 7 g/l of agar along with sugar 20 gm/l for root, shoot ratio and number of roots. The best hardening was achieved in a mixture of soil : soilrite (1 : 1) where the survival rate was 94%. Further, for callus formation the best result was obtained in the leaf explants on MS supplemented with 0.5 mg/l 2, 4-D. HPLC and HPTLC profile of regenerated shoots revealed a phytochemicals profile similar to that of the market samples and mother plants. The presence of bacoside was detected through HPTLC and HPLC.    Key words:  Bacopa monnieri, Micropropagation, Bacoside   D.O.I. 10.3329/ptcb.v20i2.6890   Plant Tissue Cult. & Biotech. 20(2): 119-125, 2010 (December)